2022
DOI: 10.5194/gmd-15-173-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling reservoir surface temperatures for regional and global climate models: a multi-model study on the inflow and level variation effects

Abstract: Abstract. The complexity of the state-of-the-art climate models requires high computational resources and imposes rather simplified parameterization of inland waters. The effect of lakes and reservoirs on the local and regional climate is commonly parameterized in regional or global climate modeling as a function of surface water temperature estimated by atmosphere-coupled one-dimensional lake models. The latter typically neglect one of the major transport mechanisms specific to artificial reservoirs: heat and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Likewise, Almeida et al. (2022) compared the prediction capabilities of FLake and the Hostetler models in reproducing LSWT against a ML algorithm in 24 reservoirs where temperature dynamics are substantially affected by inflows/outflows. They found that ML models may outperform process‐based physical models in terms of both accuracy and computational cost when long‐term observations were available.…”
Section: Emerging Modeling Approaches and Future Directionsmentioning
confidence: 99%
“…Likewise, Almeida et al. (2022) compared the prediction capabilities of FLake and the Hostetler models in reproducing LSWT against a ML algorithm in 24 reservoirs where temperature dynamics are substantially affected by inflows/outflows. They found that ML models may outperform process‐based physical models in terms of both accuracy and computational cost when long‐term observations were available.…”
Section: Emerging Modeling Approaches and Future Directionsmentioning
confidence: 99%
“…To the best of our knowledge, no one has applied an MME approach to forecasting lake and reservoir temperatures with specified uncertainty. While MMEs for water temperatures have been applied to long‐term projections (Almeida et al., 2022; Feldbauer et al., 2022; La Fuente et al., 2022; Wynne et al., 2023), or as model inter‐comparisons (Golub et al., 2022), the utility of MMEs for real‐time water temperature forecasting remains unknown. This gap may exist because ensemble near‐term forecasts have, to date, focused on using ensembles of multiple driver data sets (e.g., weather forecasts; Mercado‐Bettín et al., 2021) and parameter sets (e.g., Thomas et al., 2020) to partition and quantify uncertainty (Clayer et al., 2023; Thomas et al., 2020), rather than using multiple models to generate more skillful operational forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of atmospheric reanalysis has increased significantly. Global reanalysis is now an established and frequently used source of climate data for a broad range of applications (e.g., Almeida et al, 2015; Almeida et al, 2022; Tarek et al, 2020; Vanella et al, 2020) including the energy sector (Kaspar et al, 2020). These datasets are generated by a global NWP model and a data assimilation system considering observed historical meteorological data with the aim of increasing weather condition consistency (Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%